Recent advances in acoustofluidic separation technology in biology - Yanping Fan; Xuan Wang; Jiaqi Ren; Francis Lin; Jiandong Wu (Microsystems & Nanoengineering, 2022)
Abstract Acoustofluidic separation of cells and particles is an emerging technology that integrates acoustics and microfluidics. In the last decade, this technology has attracted significant attention due to its biocompatible, contactless, and label-free nature. It has been widely validated in the separation of cells and submicron bioparticles and shows great potential in different biological and biomedical applications. This review first introduces the theories and mechanisms of acoustofluidic separation. Then, various applications of this technology in the separation of biological particles such as cells, viruses, biomolecules, and exosomes are summarized. Finally, we discuss the challenges and future prospects of this field.